2017
DOI: 10.1063/1.4986615
|View full text |Cite
|
Sign up to set email alerts
|

Photoexcited-carrier transport in barium strontium titanate/strontium titanate heterostructures

Abstract: Photoexcited-carrier transport properties at the surface and the interface of barium strontium titanate/strontium titanate heterostructures are reported. Under a 365 nm light irradiation, the surfaces of barium strontium titanate films exhibit a metal-to-insulator transition, while the interfaces favor the metallic conduction with increasing temperatures. By analyzing, we consider that these results might be attributed to the intrinsic features of strontium titanate and the polarization state of barium stronti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 42 publications
0
5
0
Order By: Relevance
“…[24,25] As a powerful external perturbation, light also can modify the transport properties of complex oxides. [26][27][28][29][30][31][32][33][34] In fact, the sensitivity of LAO/STO to the light was discovered several years ago. [35] More recently, the investigation of transport properties of light-illuminated samples revealed its fundamental physics for potential applications, which has drawn a lot of attention.…”
Section: Introductionmentioning
confidence: 99%
“…[24,25] As a powerful external perturbation, light also can modify the transport properties of complex oxides. [26][27][28][29][30][31][32][33][34] In fact, the sensitivity of LAO/STO to the light was discovered several years ago. [35] More recently, the investigation of transport properties of light-illuminated samples revealed its fundamental physics for potential applications, which has drawn a lot of attention.…”
Section: Introductionmentioning
confidence: 99%
“…Several reports have been made on the changes in the transport properties and resistivity of oxide films on the STO substrate in the energy range of ∼3.3–6 eV. Interestingly, this effect falls within region III of our study (Figure a,b) where the resonant excitonic effects are prominently observed. These reported observations support our claims on the effects of resonant excitons within this energy region such that the electron–hole pairs generated from the STO substrate propagate into the top thin film structure.…”
Section: Discussionmentioning
confidence: 74%
“…[124] These results may be useful in developing potential applications of heterojunctions for optoelectronic detections. [125][126][127][128][129][130][131]…”
Section: Manganites/bfo Heterostructuresmentioning
confidence: 99%